SNA metrics in the analysis of international trade measured by added value – the example of the EU trade network - Nacewska-Twardowska, Aleksandra; Brózda-Wilamek, Dominika (Publishing House of Wroclaw University of Economics and Business, 2024)
Research background: Dynamic changes in the trade network are evidence of the rapid development of the world economy. There is a need to analyse these transformations in the 21st century. A comprehensive description of the adjustments in the European Union trade network in terms of value added has not yet been carried out in the literature, especially in the context of network analysis. Purpose of the article: The paper presents the changes in the European Union trade network structure measured by value added and in gross terms in the years 2005 and 2018 using social network analysis (SNA). This study makes it possible to verify whether the proposed new research methodology will find confirmation in the conclusions of the research carried out with the use of other methods. Methods: For this purpose, the authors proposed applying SNA metrics to trade data, including density, weighted degree centrality, average link strength of vertex, and the PageRank algorithm. The analysis used trade data measured by value added and gross terms from the OECD trade in value added (TiVA) database for 65 economies in 2005 and 2018. Value added & findings: The literature lacks comprehensive analyses of trade value added data by using SNA metrics. The use of SNA in the study demonstrated different complexities of the EU trade network measured in gross and value added data. This confirmed that gross trade data were overestimated and did not indicate actual connections between economies. Networks based on data on trade in value added are much less developed and only consist of real connections between economies without ‘intermediary countries’. Changes in the connections between European countries in 2005 and 2018 reflect the changes occurring in the global economy, resulting in the decreasing share of the United States and Japan in the European Union trade network in favour of China. The results of the conducted research confirm the great effectiveness of the SNA methodology in the analysis of trade links in the context of the networks created by the analysed entities.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 159-175
Keywords: international trade; European Union; value added; social network analysis; degree centrality